Industrial Development in Cities - Henderson, Vernon; Kuncoro, Ari; Turner, Matt (Journal of Political Economy, 1995)
This paper uses data for eight manufacturing industries in 1970 and 1987 to test for and characterize dynamic production externalities in cities. We find evidence of both MAR externalities, which are associated with past own industry employment concentration, and Jacobs externalities, which are associated with past diversity of local total employment. More specifically, for mature capital goods industries, there is evidence of MAR externalities but none of Jacobs externalities. For new high-tech industries, there is evidence of Jacobs and MAR externalities. These findings are consistent with notions of urban specialization and product cycles: new industries prosper in large, diverse metropolitan areas, but with maturity, production decentralizes to smaller, more specialized cities. For mature industries, there is also a high degree of persistence in individual employment patterns across cities, fostered by both MAR externalities and persistence in regional comparative advantage.